Encapsulated virgin coconut oil as a nanoscale in vitro solution against multiple drug resistant Staphylococcus aureus. (29th December 2020) - Talib, A.; Manzoor, K. N.; Ijaz, A.; Adnan, F.; Javed, F.; Khan, A. A.
Abstract: Niosomes are excellent nanoscale vehicular systems that can carry a variety of drugs and (bioactive) compounds entrapped inside them. Virgin coconut oil (VCO) is the finest grade of coconut oil that is highly enriched with phenolic content, antioxidant activity and also comprises medium chain triglycerides. In this work, niosomes were encapsulated with VCO synthesized by a simple chemical method. The electron microscopy confirmed that spherical nanostructured lipid carrier molecules with a diameter in the range of 180–190 nm were produced. A zeta potential value of −42 mV was a testimony that these nanovehicles were having good stability. The natural oil loaded nanocarrier spheres proved to be potent antibacterial nano‐antibiotics against multiple drug resistant (MDR) bacteria. The antibacterial activity of these magic nano‐spheres was found to be better than ZnO (metallic oxides) nanoparticles. The nano‐antibiotics resulted in 17, 14 and 12 mm zones of inhibition against methicillin‐resistant Staphylococcus aureus (MRSA), vancomycin‐resistant S. aureus (VRSA) and a (general) MDR strain of S. aureus in contrast to nanoparticles that resulted in zones of inhibitions 7, 8 and 6 mm for the same bacterial strains. Niosomes prove to be an excellent nanocarrier system that can encapsulate a number of bio‐active compounds.